(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to clarify the concept of internal control as an important tool in the service of management because of its fundamental role in ensuring the safety of work and addressing deviations. The research problem was the increase in tax expenditures, so the research problem emerged from the question (Does internal control have an impact on tax spending?) and aims the current research seeks to verify the effect of internal control as an independent variable and the rationalization of tax spending as a responsive variable, in addition to identifying the levels of its practices. Therefore, the importance of the research comes in that it sheds light on the reality of internal control and the importance of this function in the availability of decent work and the growth of the economy, based on the importance of the research topic. In public organizations, its importance to the General Authority for Taxes and society, and the variable dependent on tax expenditures, and the economic unit studied was (the General Authority for Taxes), as the descriptive and analytical approach was used, relying on taking practical cases from the reality of the General Authority for Taxes for each form or form of tax expenditures, that The research sample was in the senior taxpayers section of two companies for the period (from 2020 to 2021). It relied on the disclosure of ongoing operations to determine the revenues for each fiscal year, and the tools adopted in the process of analyzing data and financial statements were based on the annual controls issued by the General Authority for Taxes, which express financial ratios relied upon by the authority to subject the taxpayer to tax, and within the framework of discussing the results, the researcher presented a number of The most important conclusions are that oversight implements and applies laws, regulations, and instructions that contribute to facilitating the completion of daily transactions as well as increasing tax revenues by applying the annual controls issued by the General Authority for Taxes. The researcher also presented a number of recommendations, the most important of which is the necessity of the taxpayer reviewing the General Authority for Taxes to determine the exempt taxes. The taxes that must be paid to the General Authority for Taxes - Department of Direct Deduction imposed on workers according to Income Tax No. 113 of 1982, as amended.